Global burden of varicella and herpes zoster across 204 countries, 1990–2021: a temporal trend analysis in the era of the COVID-19 pandemic and projections to 2036 - Wu, Zilun; Zhang, Jinbu; Wei, Jiahao; Huang, Chenjin; Xu, Weibang; Wu, Jiaqiang; Jiang, Meirong (Frontiers in Public Health, 2025)
ObjectiveTo assess the temporal trends and regional disparities of the disease burden of varicella and herpes zoster across 204 countries from 1990 to 2021, analyze the impact of the COVID-19 pandemic era, and project sex-specific incidence trends to 2036.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021 study, we analyzed the incidence, mortality, and disability-adjusted life years (DALYs) of varicella and herpes zoster. Joinpoint regression analysis identified significant shifts in temporal trends, treating 2019 as a key inflection point to observe the pandemic’s impact. A Bayesian Age-Period-Cohort (BAPC) model was used to project future incidence trends. Analyses were stratified by region, sex, age, and Socio-demographic Index (SDI), and frontier analysis was applied to evaluate the efficiency of health burden management.ResultsFrom 1990 to 2021, global varicella and herpes zoster cases increased by 19.0% (72.8 to 86.7 million), while age-standardized incidence rates (ASIR) remained stable. Mortality and DALYs declined significantly, with age-standardized mortality rates (ASMR) and DALYs rates (ASDR) decreasing by 50.0 and 36.3%, respectively. A stark disparity remains, with low-SDI regions accounting for over 67% of deaths and DALYs. High-SDI regions, conversely, exhibited a resurgence in varicella and herpes zoster (ASIR: 1,300/100,000) driven by aging populations. The burden followed a U-shaped curve by age, with children <5 years having the highest incidence and adults ≥45 years facing elevated mortality. BAPC modeling projected gradual declines in ASIR for both sexes by 2036.ConclusionThe dual burdens of varicella and herpes zoster in low-SDI regions and aging-driven herpes zoster resurgence in high-SDI areas necessitate targeted strategies. These include prioritizing pediatric varicella immunization and equitable vaccine distribution in developing nations while enhancing adult herpes zoster booster programs and surveillance in developed ones to meet WHO 2030 targets.